Fifty years of research on psychosocial working conditions and health: From promise to practice - Cécile RL Boot; Anthony D LaMontagne; Ida EH Madsen (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: This paper presents an overview of 50 years of research on psychosocial working conditions and health with regards to conceptualization, interventions and policy. We reflect on the promise of past and current research on psychosocial working conditions and, in addition, discuss current progress in translating this research into workplace practice and improvements in people's working lives. METHODS: We conducted a narrative review of meta-reviews and key publications on psychosocial working conditions and health. The review covers a historical overview of theories of the past 50 years, measurement of psychosocial working conditions, health effects, intervention research, and policy development on psychosocial working conditions. RESULTS: Psychosocial working conditions are conceptualized in different ways, with increasing complexity in the understanding developing over time. Exposures related to psychosocial working conditions are associated with a wide range of health outcomes, in particular cardiovascular disease and mental health conditions. In response to growing evidence on associations between psychosocial working conditions and health outcomes, intervention research has expanded rapidly, but for various reasons the evidence base is stronger and more extensive for individual- than organizational-level interventions. This individual/organizational imbalance is reflected in practice, and may partly explain why policy interventions have yet to show reductions in exposures to psychosocial work factors and associated adverse outcomes. CONCLUSIONS: Pressing needs for advancing the field include improvements in capturing exposure dynamics, developing objective measures of exposure, methodologic advancements to optimize causal inference in etiologic studies, and alternatives to randomized controlled trials for intervention evaluation.